An Overview of Neurotrauma Care in UCMS and GTB Hospital, New Delhi - Sarma, Pragyan; Garg, Manish (Indian Journal of Neurotrauma, 2023)
University College of Medical Sciences (UCMS) and the associated Guru Teg Bahadur Hospital (GTBH) is one of the largest tertiary care centers in the National capital of Delhi. It caters to a large volume of patients mainly from north east Delhi along with neighboring states of Uttar Pradesh and Haryana. Since the establishment of neurosurgery department in 1997, the department has contributed significantly toward neurotrauma care. With the upgradation of infrastructure in recent years, the department surely has a bright future in neurotrauma services benefiting a huge population. In this article, I have tried to describe the brief history of neurotrauma care, present status of manpower, and infrastructure to manage trauma patients, difficulties yet to overcome and roadmap for future.
Keywords: GTBH; UCMS; neurotrauma; cranial; spinal